Characterization of the complete chloroplast genome of Aquilaria sinensis, an endangered agarwood-producing tree - Xin Deng; Zhenxing Jiang; Qingbin Jiang; Wei Guo; Yongquan Li; Xianzhi Zhang (Mitochondrial DNA. Part B. Resources, 2020)
Aquilaria sinensis is one of the most important agarwood-producing trees but critically endangered at present. In this study, we produced the complete chloroplast (cp) genome of A. sinensis via genome survey analysis. The assembled genome is 174,914 base-pairs (bp) in length, with one large single-copy region of 87,361 bp and one small single-copy region of 3347 bp separated by two inverted repeats of 42,103 bp. The genome contains a total of 142 genes, including 96 protein-coding genes, 8 rRNAs, and 38 tRNAs. The phylogenomic tree strongly supports Aquilaria as a monophyly and A. sinensis sister to A. yunnanensis.